Systematic Literature Review: Teacher Learning Communities as a Strategy for Sustainable Professional Development in Schools - Agustina, Ade Erma; Riswandi, Riswandi; Sari, Siti Rahma (Universitas Sang Bumi Ruwa Jurai, 2025)
This research aims to examine the role of Professional Learning Communities (PLC) or Teacher Learning Communities as a strategy for sustainable professional develssopment in schools. This study uses a Systematic Literature Review method to select and review 20 relevant scientific articles, published in the period 2020–2024. The focus of the analysis is directed at four research questions, which include effective PLC implementation models, the benefits of PLC in schools, challenges in its implementation, and institutional support for the success of PLC. The study results show that effective PLCs are characterized by teacher collaboration that is structured, reflective, and data-based. The main benefits of PLC include increasing teacher competency, work motivation, and collaborative culture. However, the challenges that arise include limited time, lack of leadership support, low teacher participation, and a work culture that is still individualistic. Institutional support, such as principals, school policies, and facilitator training, is proven to play an important role in the success of PLC implementation. In conclusion, PLC can be an effective strategy in improving the quality of learning and teacher professional development if implemented consistently and supported by a supportive school system.